Lightweight high-strength glass-magnesium plate and preparation method thereof

CN123003252APending Publication Date: 2026-10-30HUIZHOU WEIYUEHONG NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611208359.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]本发明的目的是提供一种轻质高强度玻镁板及其制备方法,解决板材自重大幅增加建筑主体结构荷载,抬高钢结构、楼板承重设计成本以及在南方梅雨、沿海盐雾、地下室高湿环境下,水分沿板材内部毛细孔迁移至板面,可溶性镁盐、氯盐析出形成白色霜层,严重时板面渗出粘稠卤水,造成饰面起皮、变色,长期接触轻钢龙骨、自攻螺钉会造成金属锈蚀、连接松动,吊顶、隔墙存在脱落安全隐患的问题

Benefits of technology

[0015]本发明所述的一种轻质高强度玻镁板及其制备方法优点和积极效果是:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003252A_ABST
    Figure CN123003252A_ABST
Patent Text Reader

Abstract

The application discloses a light high-strength glass magnesium plate and a preparation method thereof, and belongs to the technical field of glass magnesium plates. The light high-strength glass magnesium plate comprises a base body, a filler, a multilayer reinforcing framework and an improver, and the base body is made of the following raw materials: 40-50 parts of magnesium oxide, 20-30 parts of 30 Baume magnesium chloride-magnesium sulfate composite brine, 10-18 parts of 800-mesh heavy calcium carbonate powder and 8-15 parts of polystyrene particles. The five core technologies of composite halogen inhibition brine, hierarchical closed-cell foaming, sandwich buffer reinforcing framework, silica ash-fiber toughening and composite low-shrinkage setting aid are synergized, and the five core advantages of light weight, high strength, low shrinkage, long-acting anti-halogen return and stable interlayer combination are simultaneously achieved. The application solves the industry pain points of the traditional glass magnesium plate, such as large self-weight, easy halogen return, poor toughness and easy cracking, and easy interlayer delamination and hollowing, has strong universality, and is suitable for various building scenes, such as home decoration ceiling, indoor partition wall, industrial plant enclosure and ventilation pipeline base plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of magnesium oxide board technology, and in particular to a lightweight, high-strength magnesium oxide board and its preparation method. Background Technology

[0002] Magnesium oxide (MgO) board, also known as magnesium chloride-based fireproof board, is an air-hardening magnesium cementitious composite material. Its core cementing phase is 5Mg(OH)₂·MgCl₂·8H₂O, formed by the hydration of magnesium oxide and magnesium salt brine. It is composited with inorganic fillers and a fiberglass-reinforced skeleton, making it a mainstream Class A non-combustible board in China's prefabricated building, fire ventilation, and interior decoration fields. Compared to paper-faced gypsum board, cement fiberboard, and calcium silicate board, magnesium oxide board offers comprehensive advantages such as non-combustibility, water resistance, moisture resistance, low production cost, and compatibility with various surface coatings. It is widely used in basement duct cladding, hotel partitions, shopping mall ceilings, fireproof cladding of steel structures, and cleanroom enclosures.

[0003] Traditional standard magnesium oxide boards use only 800-mesh calcium carbonate as a single filler, without a foaming system or lightweight EPS particles. The apparent density of these boards is generally 1.3–1.6 g / cm³. 3 When constructing large-area suspended ceilings and long-span partition walls in high-rise residential buildings, the self-weight of the panels significantly increases the load on the main building structure, raising the design costs of steel structures and floor load-bearing capacity. Furthermore, conventional magnesium oxide boards only use pure magnesium chloride brine as a mixing liquid, leaving a large amount of free Cl- residue within the hydration system. - Mg 2+ In the rainy season in the south, the salt fog along the coast, and the high humidity environment of basements, moisture migrates to the surface of the board through the internal capillaries. Soluble magnesium salts and chloride salts precipitate out to form a white frost layer. In severe cases, viscous brine seeps out of the board surface, causing the surface to peel and discolor. Long-term contact with light steel keel and self-tapping screws will cause metal corrosion and loosening of connections, posing a safety hazard of ceiling and partition wall falling off. Summary of the Invention

[0004] The purpose of this invention is to provide a lightweight, high-strength magnesium oxide board and its preparation method, which solves the problems of the board's self-weight significantly increasing the load on the main building structure, raising the design cost of steel structure and floor load-bearing capacity, and the fact that in the rainy season in the south, coastal salt fog, and high humidity environments in basements, moisture migrates along the capillaries inside the board to the surface, causing soluble magnesium salts and chloride salts to precipitate and form a white frost layer. In severe cases, viscous brine seeps out of the board surface, causing the surface to peel and discolor. Long-term contact with light steel keel and self-tapping screws can cause metal corrosion, loosening of connections, and potential safety hazards such as ceiling and partition wall detachment.

[0005] To achieve the above objectives, the present invention provides a lightweight, high-strength magnesium oxide board, comprising a matrix, filler, a multi-layer reinforcing skeleton, and a modifier. The matrix is ​​made from the following raw materials: 40-50 parts magnesium oxide, 20-30 parts 30 Baume degree magnesium chloride-magnesium sulfate composite brine, and 10-18 parts 800-mesh heavy calcium carbonate powder. The filler is 8-15 parts polystyrene particles. The multi-layer reinforcing skeleton consists of two layers of 70-90 g / m² alkali-free fiberglass mesh with polyester sandwiched in between. The nonwoven sandwich structure has a reinforcing skeleton whose total mass accounts for 5% to 8% of the total surface mass of the board. The modifier is made from the following raw materials: 0.1 to 0.2 parts citric acid, 0.2 to 0.4 parts sodium dihydrogen phosphate, 0.2 to 0.3 parts aluminum sulfate, 0.8 to 1.2 parts composite long-lasting halogen inhibitor modifier, 0.4 to 0.7 parts composite foam stabilizer and foaming agent, 3 to 6 parts silica fume-polypropylene fiber inorganic toughening filler, and 0.2 to 0.4 parts boric acid-triethanolamine setting regulator and low shrinkage aid.

[0006] Preferably, the mass ratio of magnesium chloride to magnesium sulfate in the magnesium chloride-magnesium sulfate composite brine is 7:3 to 9:1; the polystyrene particles are composed of 0.5-1 mm fine particles and 3-5 mm coarse particles in a ratio of 6:4 to 8:2.

[0007] Preferably, the composite long-acting halogen inhibitor modifier is prepared by mixing silane coupling agent KH-550, nano silica, and tartaric acid in a mass ratio of 2:3:5; the nano silica has a particle size of 20-50 nm.

[0008] Preferably, the composite foam stabilizer is composed of sodium dodecyl sulfate K12, silicone polyether foam stabilizer, and hydrolyzed gelatin in a mass ratio of 4:3:3; the foaming ratio is 18 to 22 times, the foam half-life is ≥4 hours, and the internal pore size of the board is 0.1 to 0.5 mm, all of which are closed-cell structures.

[0009] Preferably, the silica fume-polypropylene fiber inorganic toughening filler is a mixture of ultrafine silica fume and polypropylene fiber in a mass ratio of 8:2 to 9.5:0.5, wherein the ultrafine silica fume has a specific surface area ≥1500 m². 2 / kg, wherein the polypropylene fiber is a short-cut polypropylene fiber with a length of 4-8mm and a diameter of 10-15μm.

[0010] Preferably, the mass ratio of boric acid to triethanolamine in the boric acid-triethanolamine low shrinkage regulator is 0.8:1.2 to 1.2:0.8; the dry and wet shrinkage rate of the board is ≤0.15%; and the maximum temperature of the core during the curing stage does not exceed 75°C.

[0011] A method for preparing a lightweight, high-strength magnesium oxide board, applicable to the aforementioned lightweight, high-strength magnesium oxide board, includes the following steps: S1: Raw material pretreatment and slurry mixing, conduct physicochemical index classification tests on all raw materials, prepare compound brine with magnesium chloride and magnesium sulfate in proportion, pre-prepare stable foam, dry mix all solid raw materials, and then slowly add compound brine and stir to obtain a uniform molding slurry without large bubbles. S2: Integrated molding by rolling and pressing. The mold is laid flat from bottom to top, with the bottom layer of fiberglass cloth, the middle layer of polyester non-woven cloth, and the top layer of fiberglass cloth. The slurry is spread evenly and then rolled by rollers to remove internal air bubbles. After reaching the standard, it is conveyed to the molding frame at a uniform speed. S3: Segmented constant temperature curing and demolding. The molded board is sent into the curing room to complete the first constant temperature and humidity curing. After curing, the qualified board is transferred to the curing workshop by a lift for the second gradient temperature controlled curing. S4: Drying, precision cutting, and finished product inspection and packaging. After curing, the boards are first laid out in layers and allowed to air dry naturally. Then, the cutting saw is calibrated to carry out the cutting operation. After the qualified boards are marked with specifications, batch and production date, they are covered with film, stacked, packaged and put into storage.

[0012] Preferably, the raw material pretreatment and slurry mixing in S1 includes: classifying and inspecting the raw materials; mixing magnesium chloride and magnesium sulfate with water at a mass ratio of 7:3 to 9:1 to prepare a 30 Baume degree composite brine and letting it stand in a sealed container for 24 hours; mixing the composite foam stabilizer with 4 to 6 times the amount of warm water for 2 to 4 minutes to prepare pre-foam; then adding all the solid raw materials into a mixer and dry mixing for 1.5 to 2.5 minutes, slowly adding the composite brine and mixing for 2.5 to 3.5 minutes, and finally mixing in the pre-foam and stirring at high speed for 3 to 5 minutes to obtain a uniform molding slurry without large bubbles.

[0013] Preferably, the segmented constant temperature curing and demolding in S3 includes a first-stage constant temperature and humidity curing, mechanical demolding, and a second-stage gradient temperature-controlled curing. The molded boards are sent to the curing room to complete the first-stage constant temperature and humidity curing. The curing time is 22-26 hours at an ambient temperature of 10-25℃ and a relative humidity of 50%-65%, and 10-14 hours at an ambient temperature of 25-35℃ and a relative humidity of 55%-70%. The core temperature is controlled to be ≤75℃. After curing, the boards are mechanically demolded using a lift and sorted one by one. The qualified boards are then transferred to the curing workshop for a second-stage gradient temperature-controlled curing. The total curing cycle is no less than 6 days, with three-stage temperature-controlled curing. The core temperature does not exceed 80℃ throughout the process. If the temperature exceeds the limit, layered isolation and forced air blowing are used to cool it down.

[0014] Preferably, in the S4 drying, precision cutting, and finished product inspection and packaging process, the cured boards are first layered and air-dried naturally in the shade. In a high-humidity environment, a drying room is used for gradient heating, with a heating rate ≤5℃ / h and a maximum drying temperature ≤50℃, until the board moisture content is ≤8%. Then, the cutting saw is calibrated to carry out the cutting operation, with a cutting height not exceeding 5cm, a feeding forward frequency of 22~28Hz, and a backward frequency of 45~55Hz. After cutting, the board dimensions are inspected, with length and width deviations controlled at ±1mm and diagonal deviations controlled at ±3mm. After inspection, the qualified boards are labeled with specifications, batch number, and production date, then laminated, stacked, packaged, and stored.

[0015] The advantages and positive effects of the lightweight high-strength magnesium oxide board and its preparation method described in this invention are as follows: This invention achieves five core advantages through the synergistic application of five core technologies: composite brine inhibition, graded closed-cell foaming, sandwich buffer reinforcement skeleton, silica fume-fiber toughening, and composite low-shrinkage setting aid. These advantages include lightweight, high strength, low shrinkage, long-lasting anti-efflorescence, and stable interlayer bonding. This invention addresses the industry pain points of traditional magnesium oxide boards, such as excessive weight, susceptibility to efflorescence, poor toughness leading to cracking, and easy delamination and hollowing between layers. It is highly versatile and suitable for various building applications, including home ceilings, interior partitions, industrial plant enclosures, and ventilation duct substrates.

[0016] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0017] Figure 1 A process flow diagram provided for embodiments of the present invention. Detailed Implementation

[0018] In this application, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains. In case of any inconsistency, the meaning set forth in this specification or derived from the content described herein shall prevail. Furthermore, the terminology used herein is for the purpose of describing embodiments of this application only and is not intended to limit the scope of this application.

[0019] The embodiments of the present invention will be described in detail below with reference to examples.

[0020] A lightweight, high-strength magnesium oxide board comprises a matrix, filler, a multi-layer reinforcing skeleton, and a modifier. The matrix is ​​made from the following raw materials: 40-50 parts magnesium oxide, 20-30 parts 30 Baume magnesium chloride-magnesium sulfate composite brine, 10-18 parts 800-mesh heavy calcium carbonate powder, and 8-15 parts polystyrene particles as filler. The multi-layer reinforcing skeleton is a sandwich structure consisting of two layers of 70-90 g / m² alkali-free fiberglass mesh with polyester nonwoven fabric sandwiched in between, and the total mass of the reinforcing skeleton accounts for 5%-8% of the total surface mass of the board. The modifier is made from the following raw materials: 0.1-0.2 parts citric acid, 0.2-0.4 parts sodium dihydrogen phosphate, 0.2-0.3 parts aluminum sulfate, 0.8-1.2 parts composite long-lasting halogen inhibitor modifier, 0.4-0.7 parts composite foam stabilizer, 3-6 parts silica fume-polypropylene fiber inorganic toughening filler, and 0.2-0.4 parts boric acid-triethanolamine setting regulator and low-shrinkage agent.

[0021] Three-layer sandwich fiberglass-nonwoven composite skeleton: The top and bottom two layers of fiberglass mesh provide overall bending load-bearing capacity, while the middle polyester nonwoven flexible buffer layer absorbs the interlayer shear stress generated by rolling and curing, preventing the fiberglass cloth from delaminating from the magnesium matrix; a single fiberglass mesh is hard and brittle, and the mesh will break directly under impact, while the middle nonwoven fabric disperses the impact load and improves the board's resistance to drop hammer impact; the total mass of the skeleton accounts for 5% to 8% of the board surface area. If the proportion is too low, the reinforcement will be insufficient, and if it is too high, the self-weight will be increased and the cost will be increased. A balance between strength and lightweight is achieved within this range.

[0022] The mass ratio of magnesium chloride to magnesium sulfate in the magnesium chloride-magnesium sulfate composite brine is 7:3 to 9:1; the polystyrene particles are composed of fine particles of 0.5 to 1 mm and coarse particles of 3 to 5 mm in a ratio of 6:4 to 8:2.

[0023] Free Cl in pure magnesium chloride brine - High content, extremely prone to re-halogenation; magnesium sulfate introduces SO4. 2- It can react with Mg in the system 2+ Stable magnesium salt crystals are generated to fix free ions and reduce ion migration from the source. The 7:3 to 9:1 ratio balances the curing speed and halogen suppression effect. If the ratio is too low, the curing is slow and the production efficiency is low. If the ratio is too high, the halogen suppression performance will decrease. Adjusting to 30 Baume degrees ensures a stable magnesium-oxygen molar ratio and avoids under-burning or over-burning, which can cause the board to pulverize and crack. Sealing and standing for 24 hours allows the salts to fully dissolve and eliminate crystallization impurities, resulting in a pinhole-free molding. Fine particles fill the tiny gaps in the matrix, while coarse particles construct a continuous lightweight cavity skeleton. The 6:4 to 8:2 compounding achieves controllable filling density, which not only significantly reduces the overall density of the board but also avoids matrix isolation and a sharp drop in flexural strength caused by single large particles. The interlocking of coarse and fine particles improves the interfacial adhesion between EPS and magnesium matrix, making it less prone to local collapse during roll forming.

[0024] The composite long-acting halogen inhibitor modifier is prepared by mixing silane coupling agent KH-550, nano silica, and tartaric acid in a mass ratio of 2:3:5; the nano silica has a particle size of 20-50 nm.

[0025] KH-550 silane coupling agent: One end has an organic group compatible with the foaming matrix, while the other end has silanol groups that chemically bond with the hydroxyl groups on the surface of magnesium oxide and calcium carbonate, forming a hydrophobic protective film on the inorganic powder surface and blocking the migration channels of magnesium and chloride ions; 20~50nm nano silica: Ultrafine particles fill the gaps between magnesium cementitious crystals, densifying the capillary channels inside the board, blocking the path of brine permeation and precipitation, and improving the density and water resistance of the board; Tartaric acid: Complexing system free Mg 2+ Ca 2+ It inhibits the crystallization and precipitation of soluble salts; the three work together to achieve long-term brine inhibition. After 50 cycles of high and low temperature dry and wet, there is no white frost or brine precipitation on the plate surface, which is different from single short-term brine inhibition additives.

[0026] The composite foam stabilizer is composed of sodium dodecyl sulfate K12, silicone polyether foam stabilizer, and hydrolyzed gelatin in a mass ratio of 4:3:3; the foaming ratio is 18 to 22 times, the foam half-life is ≥4 hours, and the internal pore size of the board is 0.1 to 0.5 mm, all of which are closed-cell structures.

[0027] K12 provides a stable foaming gas source, silicone polyether enhances the toughness of the foam film wall, and hydrolyzed gelatin thickens the foam liquid film. The combination of these three ingredients significantly extends the foam half-life to over 4 hours. Throughout the entire process of slurry mixing, spreading, and rolling, the foam does not collapse in large quantities, ensuring stable lightweighting. A foaming ratio of 18-22 times precisely controls the density of the board; too low a foaming ratio results in insignificant weight reduction, while too high a foaming ratio leads to a decrease in mechanical strength. The 0.1-0.5mm micro-closed-cell structure isolates moisture conduction, reducing the board's water absorption rate, while simultaneously dispersing curing thermal stress and reducing drying shrinkage and cracking. Open-cell foam is prone to water absorption and efflorescence; this solution's fully closed-cell structure simultaneously improves lightweighting, waterproofing, and dimensional stability.

[0028] The silica fume-polypropylene fiber inorganic toughening filler is a mixture of ultrafine silica fume and polypropylene fiber at a mass ratio of 8:2 to 9.5:0.5, with the ultrafine silica fume having a specific surface area ≥1500 m². 2 / kg, the polypropylene fiber is short-cut polypropylene fiber with a length of 4-8mm and a diameter of 10-15μm.

[0029] High specific surface area ultrafine silica fume: Active SiO2 and magnesium cement hydration products undergo secondary hydration to generate dense magnesium silicate gel, which fills microcracks in the matrix and improves the density and flexural strength of the board; 4~8mm short-cut fine denier polypropylene fibers: uniformly dispersed in the matrix to form a three-dimensional fiber network. When subjected to impact and bending, the fibers bear tensile stress, prevent the propagation of microcracks, and significantly improve impact resistance and flexural strength; the fiber content is strictly controlled, as excessive content can easily lead to agglomeration and delamination defects; the inorganic phase of silica fume and organic fibers work synergistically to compensate for the brittleness of pure magnesium cementitious materials.

[0030] The mass ratio of boric acid to triethanolamine in the boric acid-triethanolamine setting and low shrinkage additive is 0.8:1.2 to 1.2:0.8; the dry and wet shrinkage rate of the board is ≤0.15%, and the maximum temperature of the core during the curing stage does not exceed 75℃.

[0031] Boric acid slows down the curing and temperature control: It delays the rapid hydration and heat release of magnesium cement, avoiding the excessive heat release in a short period of time after molding that could cause the core to overheat and the internal thermal stress cracking of the board, limiting the core temperature to ≤75℃; Triethanolamine promotes curing and densification: It improves the hydration of magnesium oxide, reduces unreacted free magnesium oxide, and reduces the expansion and shrinkage of hydration in the later stage; The combination of the two balances the curing rate, shortens the curing cycle, and controls the dry and wet shrinkage to ≤0.15%, which greatly reduces the cracking problem of ceiling and partition wall splicing joints.

[0032] Reference Figure 1 As shown, a method for preparing a lightweight high-strength magnesium oxide board, applicable to the aforementioned lightweight high-strength magnesium oxide board, includes the following steps: S1: Raw material pretreatment and slurry mixing, conduct physicochemical index classification tests on all raw materials, prepare compound brine with magnesium chloride and magnesium sulfate in proportion, pre-prepare stable foam, dry mix all solid raw materials, and then slowly add compound brine and stir to obtain a uniform molding slurry without large bubbles. S2: Integrated molding with mesh laying and rolling. The mold is laid flat from bottom to top, with a bottom layer of fiberglass cloth, a middle layer of polyester non-woven fabric, and an upper layer of fiberglass cloth. The slurry is spread evenly and then rolled by rollers to remove internal air bubbles. After reaching the standard, it is conveyed evenly to the molding frame, and a sandwich skeleton is prefabricated in layers. One-time mesh laying eliminates the need for secondary lamination, improving production efficiency. The roller rolling pressure evenly removes large air bubbles trapped inside the slurry, improving the bonding strength between the skeleton and the magnesium matrix interface and preventing interlayer voids and peeling. The EPS particles and foam cavities are compacted simultaneously to prevent local collapse and deformation after demolding, ensuring the flatness and thickness uniformity of the board surface. S3: Segmented constant temperature curing and demolding. The molded board is sent into the curing room to complete the first constant temperature and humidity curing. After curing, the qualified board is transferred to the curing workshop by a lift for the second gradient temperature controlled curing. S4: Drying, precision cutting, and finished product inspection and packaging. After curing, the boards are first laid out in layers and allowed to air dry naturally. Then, the cutting saw is calibrated to carry out the cutting operation. After the qualified boards are marked with specifications, batch and production date, they are covered with film, stacked, packaged and put into storage.

[0033] S1 raw material pretreatment and slurry mixing includes: grading and inspecting raw materials to remove magnesium oxide lumps, coarse impurities, and EPS powder, preventing large particles from causing blistering and perforation on the board surface; testing magnesium oxide activity and brine Baume degree to ensure the hydration stability of each batch of gelling system; mixing magnesium chloride and magnesium sulfate with water at a mass ratio of 7:3 to 9:1 to prepare a 30 Baume degree composite brine and allowing it to stand in a sealed container for 24 hours to eliminate supersaturated salt crystals and avoid pinholes and pores in the molded board; and mixing the composite foam stabilizer with 4 to 6 times its volume of warm water for 2 to 4 minutes to prepare... Pre-mix the foam; then put all the solid raw materials into the mixer and dry mix for 1.5 to 2.5 minutes. Slowly add the compound brine and mix for 2.5 to 3.5 minutes. Finally, mix in the pre-mixed foam and mix at high speed for 3 to 5 minutes to obtain a uniform molding slurry without large air bubbles. The solid phase is first dry mixed to ensure that magnesium oxide, calcium carbonate, silica fume and fiber are evenly dispersed and to prevent fiber agglomeration. The brine is pre-mixed at low speed to build a magnesium gelation base system. Finally, the foam is mixed in at low speed to prevent high-speed shear from puncturing the foam cells and to retain the complete closed-cell lightweight structure. The slurry is free of large air bubbles and the board surface is flat and free of pits after rolling.

[0034] The S3 segmented constant temperature curing and demolding process includes primary constant temperature and humidity curing, mechanical demolding, and secondary gradient temperature-controlled curing. The molded sheets are placed in a curing room for primary constant temperature and humidity curing at an ambient temperature of 10–25℃ and relative humidity of 50%–65% for 22–26 hours; then at an ambient temperature of 25–35℃ and relative humidity of 55%–70% for 10–14 hours, with the core temperature controlled ≤75℃. After curing, a lift is used for mechanical demolding, and the sheets are sorted one by one. Qualified sheets are then transferred to the curing workshop for secondary gradient temperature-controlled curing. The total curing cycle is no less than [number missing]. Over six days, the material undergoes three stages of temperature-controlled curing, ensuring the core temperature does not exceed 80℃ throughout the process. If the temperature exceeds this limit, layered isolation and forced air cooling are employed to reduce the temperature. This staged curing process addresses the issues of uneven hydration and thermal cracking caused by single high-temperature curing. The first stage of low-temperature, long-duration curing allows the surface magnesium cement to fully solidify and prevents demolding deformation. The gradient secondary curing process slowly releases the heat of hydration, ensuring complete hydration of magnesium oxide in the core of the material, reducing the content of free magnesium oxide, and minimizing subsequent efflorescence, expansion, and contraction. Forced air cooling and temperature control prevent heat accumulation and overheating of the core, significantly reducing the scrap rate and improving the long-term dimensional stability of the material.

[0035] In the S4 drying, precision cutting, and finished product inspection and packaging process, the cured boards are first layered and naturally air-dried in the shade. In high-humidity environments, a gradient temperature drying chamber is used, with a heating rate ≤5℃ / h and a maximum drying temperature ≤50℃, until the board moisture content is ≤8%. Subsequently, the cutting saw is calibrated for cutting operations, with a cutting height not exceeding 5cm, a feeding forward frequency of 22~28Hz, and a backward frequency of 45~55Hz. After cutting, the board dimensions are inspected, with length and width deviations controlled within ±1mm and diagonal deviations controlled within ±3mm. After inspection, the qualified boards are labeled with specifications, batch number, and production date, then laminated, stacked, packaged, and stored. Low-temperature gradient drying avoids rapid water loss at high temperatures that could cause board shrinkage and cracking, and controlling the moisture content to ≤8% reduces moisture migration and efflorescence at the user end. Precise cutting frequency and height control ensure a flat, chip-free cut surface, and dimensional tolerances strictly meet the requirements of prefabricated building installation. Lamination isolates the boards from moisture in the storage and transportation environment, preventing frost formation during storage. Complete batch labeling enables product quality traceability.

[0036] Example 1 A lightweight, high-strength magnesium oxide board comprises a matrix, filler, a multi-layer reinforcing skeleton, and a modifier. The matrix is ​​made from the following raw materials: 45 parts magnesium oxide, 25 parts 30 Baume composite brine (with a magnesium chloride:magnesium sulfate ratio of 8:2), and 14 parts 800-mesh heavy calcium carbonate. The filler consists of 11 parts polystyrene particles (0.8mm fine particles: 4mm coarse particles in a 7:3 ratio). The multi-layer reinforcing skeleton consists of two layers of 80g / m² alkali-free fiberglass with a polyester non-woven fabric in between, and the skeleton accounts for 6.5% of the board's surface weight. The modifier is made from the following raw materials: 0.15 parts citric acid, 0.3 parts sodium dihydrogen phosphate, 0.25 parts aluminum sulfate, 1.0 part composite long-lasting halogen inhibitor, 0.55 parts composite foam stabilizer and foaming agent, and 4.5 parts silica fume-polypropylene toughening filler, wherein the ratio of ultrafine silica fume to polypropylene fiber is 9:1, the polypropylene fiber length is 6mm, the diameter is 12μm, and the specific surface area of ​​silica fume is 1650m². 2 / kg, 0.3 parts of boric acid-triethanolamine auxiliaries, wherein boric acid:triethanolamine = 1:1; The compound long-lasting halogen inhibitor modifier has the following ratio: KH-550: nano silica: tartaric acid = 2:3:5, and the nano silica has a particle size of 35nm. The composite foam stabilizer and foaming agent has the following ratio: sodium dodecyl sulfate K12: silicone polyether foam stabilizer: hydrolyzed gelatin = 4:3:3, with a foaming ratio of 20 times, a foam half-life of 4.2h, and fully closed-cell cells of 0.2~0.4mm. The method for preparing lightweight, high-strength magnesium oxide board includes the following steps: S1: Raw material inspection, brine preparation and sealing for 24 hours; foaming agent is mixed with 5 times the amount of warm water for 3 minutes to pre-make foam; all solid phases are dry mixed for 2 minutes, brine is added and stirred for 3 minutes, foam is mixed in and stirred at high speed for 4 minutes. S2: Bottom layer fiberglass → polyester nonwoven fabric → upper layer fiberglass mesh laying, uniform fabric feeding, roller pressing to remove bubbles, and feeding into the forming frame. S3: First curing environment 20℃, humidity 60% curing for 24 hours, core temperature up to 72℃; mechanical demolding and sorting; second gradient curing total cycle 7 days, core temperature up to 78℃, ultra-high temperature air cooling; S4: Layered, air-dried naturally until moisture content reaches 7.2%; cut with a cutting saw at 25Hz feed and 50Hz back, with dimensional tolerance ±0.8mm, inspected, laminated, and put into storage.

[0037] Example 2 A lightweight, high-strength magnesium oxide board includes a matrix, filler, multi-layer reinforcing skeleton, and modifier. The matrix is ​​made of the following raw materials: 40 parts magnesium oxide, 20 parts 30 Baume composite brine, wherein magnesium chloride: magnesium sulfate = 7:3, and 10 parts 800 mesh heavy calcium carbonate. The filler consists of 8 parts polystyrene (EPS) particles, with a ratio of 0.5mm fine particles to 3mm coarse particles of 6:4. The multi-layer reinforced skeleton consists of two layers of 70g / ㎡ alkali-free fiberglass on the top and bottom, with polyester non-woven fabric in the middle, and the skeleton accounts for 5% of the board surface weight; The modifier is made from the following raw materials: 0.1 parts citric acid, 0.2 parts sodium dihydrogen phosphate, 0.2 parts aluminum sulfate, 0.8 parts composite long-lasting halogen inhibitor, 0.4 parts composite foam stabilizer and foaming agent, and 3 parts silica fume-polypropylene toughening filler, wherein the ratio of ultrafine silica fume to polypropylene fiber is 8:2, the polypropylene fiber is 4mm / 10μm, and the specific surface area of ​​silica fume is 1500m². 2 / kg, 0.2 parts of boric acid-triethanolamine adjuvant, wherein boric acid:triethanolamine = 0.8:1.2.

[0038] The composite long-lasting halogen inhibitor modifier has a formulation ratio of KH-550: nano silica: tartaric acid = 2:3:5, with a nano silica particle size of 20nm; the foam stabilizer has a foaming ratio of 18 times and a foam half-life of 4.0h; The method for preparing lightweight, high-strength magnesium oxide board includes the following steps: S1: Raw material inspection, brine preparation and sealing for 24 hours; foaming agent is mixed with 5 times the amount of warm water for 3 minutes to pre-make foam; solid phase dry mixing for 1.5 minutes, brine is added and stirred for 2.5 minutes, foam is mixed in and stirred at high speed for 3 minutes. S2: Bottom layer fiberglass → polyester nonwoven fabric → upper layer fiberglass mesh laying, uniform fabric feeding, roller pressing to remove bubbles, and feeding into the forming frame. S3: First curing environment 30℃, humidity 65% ​​curing for 12 hours, core temperature ≤73℃; Second curing total cycle 6 days; S4: Gradient drying in a high-humidity environment, temperature rise of 4℃ / h, maximum 45℃, moisture content 7.8%, then cutting and packaging.

[0039] Example 3 A lightweight, high-strength magnesium oxide board includes a matrix, fillers, a multi-layer reinforcing skeleton, and modifiers. The matrix is ​​made of the following raw materials: 50 parts magnesium oxide, 30 parts 30 Baume composite brine, wherein magnesium chloride: magnesium sulfate = 9:1, and 18 parts 800-mesh heavy calcium carbonate. The filler consists of 15 parts polystyrene particles, of which 0.8mm fine particles and 4mm coarse particles are in a ratio of 8:2. The multi-layer reinforced skeleton consists of two layers of 90g / ㎡ alkali-free glass fiber on the top and bottom, with polyester non-woven fabric in the middle, and the skeleton accounts for 8% of the board surface mass. The modifier is made from the following raw materials: 0.2 parts citric acid, 0.4 parts sodium dihydrogen phosphate, 0.3 parts aluminum sulfate, 1.2 parts composite long-lasting halogen inhibitor, 0.7 parts composite foam stabilizer and foaming agent, and 6 parts silica fume-polypropylene toughening filler, wherein the ratio of ultrafine silica fume to polypropylene fiber is 9.5:0.5, the polypropylene fiber length is 8mm, the diameter is 15μm, and the specific surface area of ​​silica fume is 1700m². 2 / kg, 0.4 parts of boric acid-triethanolamine adjuvant, wherein boric acid:triethanolamine = 1.2:0.8.

[0040] The halogen inhibitor is nano-silica with a particle size of 50nm, the foam stabilizer has a foaming ratio of 22 times, and the foam half-life is 4.5h; The method for preparing lightweight, high-strength magnesium oxide board includes the following steps: S1: Raw material inspection, brine preparation and sealing for 24 hours; foaming agent is mixed with 5 times the amount of warm water for 3 minutes to pre-make foam; solid phase dry mixing for 2.5 minutes, brine is added and stirred for 3.5 minutes, foam is mixed in and stirred at high speed for 5 minutes. S2: Bottom layer fiberglass → polyester nonwoven fabric → top layer fiberglass mesh laying, uniform fabric laying, roller pressing to remove bubbles, fed into forming frame, thickened fiberglass skeleton mesh laying, increased rolling pressure to fully remove bubbles; S3: First curing at 15℃ and 55% humidity for 26 hours, second curing cycle is 8 days; S4: Air dry naturally until the moisture content is 6.5mm, then cut precisely and put into storage.

[0041] Comparative Example 1 Completely identical to Example 1, with only two differences: 1. Only 30 Baume pure magnesium chloride is used in the brine, without adding magnesium sulfate; 2. The composite long-lasting brine inhibitor modifier is removed, and only 0.5 parts of a commercially available single-component brine inhibitor are added; the remaining raw materials and process parameters remain unchanged.

[0042] Comparative Example 2 Completely identical to Example 1, with two differences: 1. The reinforcing skeleton eliminates the middle polyester nonwoven fabric, and only the top and bottom two layers of 80g / ㎡ glass fiber are directly bonded together; 2. The silica fume-polypropylene fiber inorganic toughening filler is removed and replaced with an equal amount of heavy calcium carbonate powder; the rest of the proportions and processes remain unchanged.

[0043] Comparative Example 3 Completely identical to Example 1, with three differences: 1. EPS consists of only 3-5mm coarse particles, without any fine particles; 2. Replaced with a local conventional foam stabilizer, with a foaming ratio of 12 times, a foam half-life of 1.2 hours, and open-cell foam in the board; 3. The boric acid-triethanolamine setting aid is removed, with only 0.3 parts of boric acid; the remaining raw materials and processes remain unchanged.

[0044] The magnesium oxide boards prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to density testing according to GB / T17657-2013 "Test Methods for Physical and Chemical Properties of Wood-based Panels for Building and Decorative Wood-based Panels"; flexural strength was tested according to GB / T2570-2020 "Test Methods for Bending Properties of Fiber Reinforced Plastics"; and the number of drop hammer non-impact cracking tests was conducted according to Appendix C of the General Impact Resistance Test Method for Building Wall Panels (GB / T23451-2021 "Lightweight Partition Wall Panels for Building"). Impact testing was conducted; the shrinkage rate after 50 wet and dry cycles was tested according to GB / T17657-2013 dimensional stability test; the 72-hour damp heat efflorescence level was tested using the general accelerated anti-efflorescence test method for the magnesium oxide building materials industry (general damp heat accelerated test specification for magnesium oxide products in the building materials industry, referring to JC / T2049-2010 "Raw Materials for Magnesium Cementitious Materials"); the interlaminar shear peel strength was determined according to GB / T1408-2006 "Test Method for Interlaminar Adhesion Strength of Insulating Materials". The performance test results of the magnesium oxide board are shown in Table 1.

[0045] Table 1 Performance test results of magnesium oxide board

[0046] As can be seen from Table 1, this invention achieves five core advantages through the synergistic effect of five core technologies: composite brine inhibition, graded closed-cell foaming, sandwich buffer reinforcement skeleton, silica fume-fiber toughening, and composite low-shrinkage setting aid. These advantages include lightweight, high strength, low shrinkage, long-lasting anti-efflorescence, and stable interlayer bonding. This solves the industry pain points of traditional magnesium oxide boards, such as excessive weight, easy efflorescence, poor toughness and easy cracking, and easy delamination and hollowing between layers. It is highly versatile and suitable for various building scenarios such as home decoration ceilings, interior partitions, industrial plant enclosures, and ventilation duct substrates.

[0047] Therefore, the lightweight high-strength magnesium oxide board and its preparation method described in this invention can solve the industry pain points of traditional magnesium oxide boards, such as excessive weight, easy efflorescence, poor toughness and easy cracking, and easy delamination and hollowing between layers.

[0048] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A lightweight, high-strength magnesium oxide board, characterized in that: The product comprises a matrix, fillers, a multi-layered reinforcing skeleton, and modifiers. The matrix is ​​made from the following raw materials: 40-50 parts magnesium oxide, 20-30 parts 30 Baume magnesium chloride-magnesium sulfate composite brine, and 10-18 parts 800-mesh heavy calcium carbonate powder. The filler is made from 8-15 parts polystyrene particles. The multi-layered reinforcing skeleton is a sandwich structure consisting of two layers of 70-90 g / m² alkali-free fiberglass mesh with polyester nonwoven fabric sandwiched in between. The total mass of the reinforcing skeleton accounts for 5%-8% of the total surface mass of the board. The modifiers are made from the following raw materials: 0.1-0.2 parts citric acid, 0.2-0.4 parts sodium dihydrogen phosphate, 0.2-0.3 parts aluminum sulfate, 0.8-1.2 parts composite long-lasting halogen-inhibiting modifier, 0.4-0.7 parts composite foam stabilizer and foaming agent, 3-6 parts silica fume-polypropylene fiber inorganic toughening filler, and 0.2-0.4 parts boric acid-triethanolamine setting regulator and low-shrinkage agent.

2. The lightweight high-strength magnesium oxide board according to claim 1, characterized in that: The magnesium chloride-magnesium sulfate composite brine has a magnesium chloride to magnesium sulfate mass ratio of 7:3 to 9:1; the polystyrene particles are composed of 0.5-1 mm fine particles and 3-5 mm coarse particles in a ratio of 6:4 to 8:

2.

3. The lightweight high-strength magnesium oxide board according to claim 2, characterized in that: The composite long-acting halogen-inhibiting modifier is prepared by mixing silane coupling agent KH-550, nano silica, and tartaric acid in a mass ratio of 2:3:5; the nano silica has a particle size of 20-50 nm.

4. The lightweight high-strength magnesium oxide board according to claim 3, characterized in that: The composite foam stabilizer is composed of sodium dodecyl sulfate K12, silicone polyether foam stabilizer, and hydrolyzed gelatin in a mass ratio of 4:3:3; the foaming ratio is 18 to 22 times, the foam half-life is ≥4 hours, and the internal pore size of the board is 0.1 to 0.5 mm, all of which are closed-cell structures.

5. The lightweight high-strength magnesium oxide board according to claim 4, characterized in that: The silica fume-polypropylene fiber inorganic toughening filler is composed of ultrafine silica fume and polypropylene fiber mixed in a mass ratio of 8:2 to 9.5:0.5, wherein the ultrafine silica fume has a specific surface area ≥1500 m². 2 / kg, wherein the polypropylene fiber is a short-cut polypropylene fiber with a length of 4-8mm and a diameter of 10-15μm.

6. The lightweight high-strength magnesium oxide board according to claim 5, characterized in that: The boric acid-triethanolamine low shrinkage modifier has a boric acid to triethanolamine mass ratio of 0.8:1.2 to 1.2:0.8; the wet and dry shrinkage rate of the board is ≤0.15%; and the maximum temperature of the core during the curing stage does not exceed 75℃.

7. A method for preparing a lightweight high-strength magnesium oxide board, applicable to the lightweight high-strength magnesium oxide board described in any one of claims 1-6, characterized in that, Includes the following steps: S1: Raw material pretreatment and slurry mixing, conduct physicochemical index classification tests on all raw materials, prepare compound brine with magnesium chloride and magnesium sulfate in proportion, pre-prepare stable foam, dry mix all solid raw materials, and then slowly add compound brine and stir to obtain a uniform molding slurry without large bubbles. S2: Integrated molding by rolling and pressing. The mold is laid flat from bottom to top, with the bottom layer of fiberglass cloth, the middle layer of polyester non-woven cloth, and the top layer of fiberglass cloth. The slurry is spread evenly and then rolled by rollers to remove internal air bubbles. After reaching the standard, it is conveyed to the molding frame at a uniform speed. S3: Segmented constant temperature curing and demolding. The molded board is sent into the curing room to complete the first constant temperature and humidity curing. After curing, the qualified board is transferred to the curing workshop by a lift for the second gradient temperature controlled curing. S4: Drying, precision cutting, and finished product inspection and packaging. After curing, the boards are first laid out in layers and allowed to air dry naturally. Then, the cutting saw is calibrated to carry out the cutting operation. After the qualified boards are marked with specifications, batch and production date, they are covered with film, stacked, packaged and put into storage.

8. The method for preparing a lightweight high-strength magnesium oxide board according to claim 7, characterized in that: The raw material pretreatment and slurry mixing in S1 include: grading and inspecting the raw materials; mixing magnesium chloride and magnesium sulfate with water at a mass ratio of 7:3 to 9:1 to prepare a 30 Baume degree composite brine and letting it stand in a sealed container for 24 hours; mixing the composite foam stabilizer with 4 to 6 times the amount of warm water for 2 to 4 minutes to prepare pre-foam; then adding all the solid raw materials to a mixer and dry mixing for 1.5 to 2.5 minutes, slowly adding the composite brine and mixing for 2.5 to 3.5 minutes, and finally mixing in the pre-foam and stirring at high speed for 3 to 5 minutes to obtain a uniform molding slurry without large bubbles.

9. The method for preparing a lightweight high-strength magnesium oxide board according to claim 8, characterized in that: The S3 segmented constant temperature curing and demolding process includes primary constant temperature and humidity curing, mechanical demolding, and secondary gradient temperature-controlled curing. The molded boards are sent to the curing room for primary constant temperature and humidity curing. Curing time is 22-26 hours at an ambient temperature of 10-25℃ and relative humidity of 50%-65%, and 10-14 hours at an ambient temperature of 25-35℃ and relative humidity of 55%-70%. The core temperature is controlled to be ≤75℃. After curing, mechanical demolding is performed using a lift, and the boards are sorted one by one. The qualified boards are then transferred to the curing workshop for secondary gradient temperature-controlled curing. The total curing cycle is no less than 6 days, with three-stage temperature-controlled curing. The core temperature does not exceed 80℃ throughout the process. If the temperature exceeds 80℃, layered isolation and forced air cooling are used to lower the temperature.

10. The method for preparing a lightweight high-strength magnesium oxide board according to claim 9, characterized in that: In the S4 drying, precision cutting, and finished product inspection and packaging process, the cured boards are first layered and naturally air-dried in a shaded environment. In a high-humidity environment, a drying chamber is used for gradient heating, with a heating rate ≤5℃ / h and a maximum drying temperature ≤50℃, until the board moisture content is ≤8%. Then, the cutting saw is calibrated to carry out the cutting operation, with a cutting height not exceeding 5cm, a feeding forward frequency of 22~28Hz, and a backward frequency of 45~55Hz. After cutting, the board dimensions are inspected, with length and width deviations controlled at ±1mm and diagonal deviations controlled at ±3mm. After inspection, the qualified boards are labeled with specifications, batch number, and production date, then laminated, stacked, packaged, and stored.